Flexible cathodes and multifunctional interlayers based on carbonized bacterial cellulose for high-performance lithium–sulfur batteries1. Issue 20 (28th May 2015) - Huang, Yang; Zheng, Mingbo; Lin, Zixia; Zhao, Bin; Zhang, Songtao; Yang, Jiazhi; Zhu, Chunlin; Zhang, Heng; Sun, Dongping; Shi, Yi
<x xml:space="preserve">Abstract</x> CBC is applied as a framework for sulfur and an interlayer in Li–S batteries. The interlayer could prevent sulfur over-aggregation on the cathode.